Three-dimensional porous multi-component alloy catalyst and preparation method thereof
The dynamic bubble template electrodeposition method is used to form a three-dimensional porous catalyst, which solves the problems of low yield, high energy consumption and difficulty in expanding the scale in the existing catalyst preparation methods, and realizes efficient and low-cost catalyst preparation, which is suitable for the electrolytic water hydrogen production process under high current density.
Patent Information
- Application Number
- CN202411971188.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-25
AI Technical Summary
The existing catalyst preparation methods have problems such as low yield, high energy consumption, and difficulty in expanding the scale. The intrinsic catalytic activity of the catalyst electrode of commercial alkaline electrolytic cell is not ideal and the overpotential is large, resulting in an increase in electricity consumption and an increase in cost.
By using the dynamic bubble template electrodeposition method, a three-dimensional porous catalyst with an open structure is formed by pretreating the matrix with a three-dimensional structure and constant current electrodeposition in the electrolyte solution.
The rapid and uniform deposition of the catalyst is achieved, forming a nanostructure with a high specific surface area, significantly improving catalytic activity, reducing preparation costs, and suitable for large-scale industrial production.
Smart Images

Figure CN119877006A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalyst preparation, and specifically relates to a three-dimensional porous multi-element alloy catalyst and a preparation method thereof. Background Art
[0002] Precious metal-based catalysts (Pt, Ir and Ru) have excellent electrocatalytic activity in the process of hydrogen production by water electrolysis, but their high cost and scarcity seriously hinder industrial production. Transition metals, such as Fe, Co and Ni and their oxides, nitrides, phosphides, sulfides and alloy compounds, are abundant in reserves, low in cost and have excellent electrocatalytic activity, and have been widely studied. Multi-metal alloy catalysts with nanostructures can regulate the electronic structure through alloying, effectively accelerating the reaction kinetics and improving the intrinsic activity of the catalyst. Another key method to improve catalytic activity is to increase the active area, which can be achieved by preparing nanostructures with high specific surface area such as nanosheets, nanoflowers and nanowires.
[0003] At present, most catalyst preparation methods involve hydrothermal or solvothermal processes and high-temperature processes, which have low yields, high energy consumption, and are difficult to scale up to meet industrial requirements. In addition, the use of some high-cost raw materials and multi-step synthesis processes also restrict the industrialization of various water electrolysis electrocatalysts. Therefore, it is extremely important to develop low-cost, simple, and repeatable catalyst preparation methods to simplify the large-scale manufacturing process of catalyst electrodes. In addition, the commercial alkaline electrolyzer catalyst electrodes currently widely used are prepared by thermal spraying Raney nickel on a nickel mesh substrate, but the intrinsic catalytic activity is not ideal, and the overpotential is large in the process of water electrolysis to produce hydrogen, which leads to an increase in electricity consumption and an increase in cost. Therefore, it is urgent to develop efficient and stable catalysts for the hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) for industrial application of water electrolysis hydrogen production catalysts at high current density. Summary of the invention
[0004] In order to overcome the problems existing in the prior art, the present invention provides a three-dimensional porous multi-element alloy catalyst and a preparation method thereof.
[0005] A method for preparing a three-dimensional porous multi-element alloy catalyst, the method comprising the following steps:
[0006] S1. pretreating the substrate having a three-dimensional structure to obtain a pretreated substrate;
[0007] S2. Connecting the pretreated substrate as a first electrode to the negative electrode of a constant current power supply, connecting the second electrode to the positive electrode of the constant current power supply, inserting the positive electrode and the negative electrode into an electrolytic cell loaded with an electrolyte solution, applying a constant current to the electrolyte solution by the constant current power supply, and performing electrodeposition on the electrolyte solution, wherein the electrolyte solution is a mixed solution including a metal salt, ammonium chloride, boric acid, sodium citrate and sodium chloride;
[0008] S3. After a period of deposition, a three-dimensional porous catalyst having an open structure is formed on the surface of the pretreated substrate;
[0009] S4. The three-dimensional porous catalyst is taken out from the electrolytic cell, rinsed and dried to obtain a three-dimensional porous multi-element alloy catalyst.
[0010] According to the above aspects and any possible implementation, an implementation is further provided, wherein the preprocessing in step S1 includes:
[0011] S11. The substrate was ultrasonically treated in acetone for 20 min to remove surface oil stains, and then rinsed three times with deionized water;
[0012] S12. The substrate obtained in S11 was then ultrasonically cleaned in 3M HCl for 20 min and then repeatedly rinsed with deionized water until the pH was neutral;
[0013] S13. The matrix obtained in S12 is ultrasonically treated with anhydrous ethanol for 20 minutes and then dried to obtain a pretreated matrix.
[0014] According to the aspects described above and any possible implementation, an implementation is further provided, wherein the substrate is one or more of nickel mesh, nickel-iron alloy mesh, copper mesh, titanium mesh, stainless steel mesh, foamed nickel, foamed iron and / or foamed copper.
[0015] According to the above aspects and any possible implementation, there is further provided an implementation, wherein the second electrode is a platinum sheet, a graphite plate or a graphite rod.
[0016] According to the aspects and any possible implementation described above, an implementation is further provided, wherein the metal salt is one or more of a nickel source, a cobalt source, an iron source, a manganese source, a copper source, a molybdenum source, and a chromium source, and the concentration range is 0.05 to 1.5 mol / L.
[0017] According to the aspects and any possible implementation described above, an implementation is further provided, wherein the concentration of ammonium chloride is 0.5-3 mol / L; the concentration of boric acid is 0.1-1 mol / L; the concentration of sodium citrate is 0.1-2 mol / L; and the concentration of sodium chloride is 0.05-0.5 mol / L.
[0018] According to the aspects described above and any possible implementation, an implementation is further provided, wherein the nickel source is nickel chloride, nickel sulfate or nickel acetate; the iron source is ferric chloride, ferrous chloride, ferric sulfate, ferrous sulfate, ferric nitrate or ferrous nitrate.
[0019] According to the above aspects and any possible implementation, an implementation is further provided, wherein the cobalt source is cobalt chloride, cobalt sulfate, cobalt acetate or cobalt nitrate; and the manganese source is manganese chloride, manganese sulfate, manganese acetate or manganese nitrate.
[0020] According to the above aspects and any possible implementation, there is further provided an implementation, wherein the constant current is 0.5 A / cm 2 ~3A / cm 2 The deposition period is 15s to 1200s.
[0021] The present invention provides a three-dimensional porous multi-element alloy catalyst, which is obtained by the method described. The pore size of the catalyst ranges from 5 to 50 μm and presents a "cauliflower", "nanoflower" or "nanosheet" nanostructure.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] The present invention provides a method for preparing a three-dimensional porous multi-element alloy catalyst, comprising: pre-treating a substrate having a three-dimensional structure to obtain a pre-treated substrate; connecting the substrate as a first electrode to the negative electrode of a constant current power supply, connecting the second electrode to the positive electrode of the constant current power supply, inserting the positive electrode and the negative electrode into an electrolytic cell loaded with an electrolyte solution, applying a constant current to the electrolyte solution by the constant current power supply, and electro-depositing the electrolyte solution. After deposition for a period of time, a three-dimensional porous catalyst with an open structure is formed on the surface of the pre-treated substrate, and after rinsing and drying, a three-dimensional porous multi-element alloy catalyst is obtained. It has the following effects: 1). The present invention adopts a dynamic bubble template electro-deposition method, and through the action of the bubble template, metal alloy materials can be deposited quickly and uniformly to form a three-dimensional porous structure. Compared with the traditional method, the preparation process of the electro-deposition method is simple and rapid, and has high operability and repeatability, does not require the use of complex equipment and high-cost precious metals, greatly reduces the preparation cost, and is suitable for large-scale industrial production. The method provides the possibility of commercializing a catalyst for hydrogen production by electrolysis of water at a high current density, and has a broad application prospect.
[0024] 2) By precisely controlling the composition of the electrolyte and the electrodeposition parameters, the morphology of the catalyst is optimized, and a three-dimensional porous, open nanostructure is achieved. This structure significantly increases the specific surface area of the catalyst and exposes more active sites, thereby significantly improving the catalytic activity, especially in the process of electrolysis of water to produce hydrogen at high current density. The regulation of the electrolyte composition mainly involves changing the type and concentration of metal salts in the electrolyte. The following examples are obtained by changing the electrolyte composition.
[0025] The present invention adopts a simple dynamic bubble template electrodeposition method to quickly and efficiently synthesize three-dimensional porous non-precious metals in one step. The non-precious metals are metal salts added to the electrolyte, such as nickel, cobalt, iron, copper, manganese, chromium and molybdenum.
[0026] Multi-element alloy nanostructured catalysts have significant price advantages over precious metal catalysts, and the raw materials are widely available; the preparation process is simple, fast, and efficient, and does not involve complex process flows such as hydrothermal or solvent thermal and high-temperature heating, which simplifies the catalyst preparation process and allows large-scale preparation of catalysts for industrial production. By adjusting the electrolyte composition and electrodeposition parameters to optimize the catalyst micromorphology, the prepared three-dimensional porous catalyst has a high specific surface area nanostructure, which can expose more active sites, optimize the contact with the electrolyte, and promote the release of gas. The prepared three-dimensional porous multi-element alloy catalyst does not require the use of a binder, enhances the interfacial charge transfer performance, and effectively accelerates the reaction kinetics. In addition, the synergistic effect of the metal elements in the multi-element alloy regulates the electronic structure and improves the conductivity. The three-dimensional porous non-precious metal multi-element alloy catalyst prepared by the present invention exhibits excellent electrochemical catalytic activity and stability in the process of hydrogen production by electrolysis of water at a high current density, and can be used for large-scale industrial applications of hydrogen production by alkaline electrolysis of water at a high current density. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a flow chart of a method for preparing a three-dimensional porous bifunctional catalyst electrode according to the present invention;
[0028] Figure 2 This is a scanning electron microscope (SEM) image of the NiCo / NM bifunctional catalyst obtained in Example 1;
[0029] Figure 3 This is a transmission electron microscope (TEM) image of the NiCo / NM bifunctional catalyst obtained in Example 1;
[0030] Figure 4 HER and OER current-voltage scanning curves of the NiCo / NM catalyst obtained in Example 1;
[0031] Figure 5 The current-voltage scanning curve of the NiCo / NM catalyst obtained in Example 1 and the current-voltage scanning curve of the NiCo / NM catalyst at 100 A / cm2 Long-term electrolysis curve under current density;
[0032] Figure 6 This is a scanning electron microscope (SEM) image of the CoFe / NF catalyst obtained in Example 2;
[0033] Figure 7 This is the OER current-voltage scanning curve of the CoFe / NF catalyst obtained in Example 2;
[0034] Figure 8 This is a scanning electron microscope (SEM) image of the NiFe / NF catalyst obtained in Example 3;
[0035] Fig. 9 This is the OER current-voltage scanning curve of the NiFe / NF catalyst obtained in Example 3;
[0036] Fig.10 This is a scanning electron microscope (SEM) image of the NiCoFe / NF bifunctional catalyst obtained in Example 4;
[0037] Fig.11 HER and OER current-voltage scanning curves of the NiCoFe / NF catalyst obtained in Example 4. DETAILED DESCRIPTION
[0038] In order to better understand the technical solution of the present invention, the content of the present invention includes but is not limited to the specific implementation methods described below, and similar technologies and methods should be considered to be within the scope of protection of the present invention. In order to make the technical problems, technical solutions and advantages to be solved by the present invention clearer, the following will be described in detail with reference to the accompanying drawings and specific embodiments.
[0039] It should be clear that the embodiments described in the present invention are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0040] The terms used in the embodiments of the present invention are only for the purpose of describing specific embodiments, and are not intended to limit the present invention. The singular forms "a", "said" and "the" used in the embodiments of the present invention and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0041] A method for preparing a three-dimensional porous multi-element alloy catalyst, the method comprising the following steps:
[0042] S1. pretreating the substrate having a three-dimensional structure to obtain a pretreated substrate;
[0043] S2. Connecting the pretreated substrate as a first electrode to the negative electrode of a constant current power supply, connecting the second electrode to the positive electrode of the constant current power supply, inserting the positive electrode and the negative electrode into an electrolytic cell loaded with an electrolyte solution, applying a constant current to the electrolyte solution by the constant current power supply, and performing electrodeposition on the electrolyte solution, wherein the electrolyte solution is a mixed solution including a metal salt, ammonium chloride, boric acid, sodium citrate and sodium chloride;
[0044] S3. After a period of deposition, a three-dimensional porous catalyst having an open structure is formed on the surface of the pretreated substrate;
[0045] S4. The three-dimensional porous catalyst is taken out from the electrolytic cell, rinsed and dried to obtain a three-dimensional porous multi-element alloy catalyst.
[0046] Specifically, the implementation process of the present invention is as follows:
[0047] Matrix pretreatment: The matrix is first ultrasonicated in acetone for 20 minutes to remove surface oil, and then rinsed repeatedly with deionized water three times. Then ultrasonically cleaned in 3M (i.e. mol / L) HCl for 20 minutes to remove surface oxides, and repeatedly rinsed with deionized water until the pH is neutral. Finally, ultrasonicated with anhydrous ethanol for 20 minutes and dried naturally for standby use. The matrix includes one or more of nickel mesh, nickel-iron alloy mesh, copper mesh, titanium mesh, stainless steel mesh, foamed nickel, foamed iron, and foamed copper. This step is performed by utilizing a matrix with a three-dimensional structure to perform in-situ synthesis of the catalyst to form a self-supporting catalyst, which can not only enhance the effective contact between the catalyst and the matrix and promote electron transfer, but also utilize the unique three-dimensional structure of the matrix to provide an efficient path for mass transfer and gas diffusion, thereby improving the overall performance of the electrocatalytic reaction.
[0048] Electrodeposition process: In a two-electrode system, a constant current power supply is used for electrodeposition. The pretreated substrate is connected to the negative electrode of the constant current power supply, and the platinum sheet, graphite plate or graphite rod is connected to the positive electrode of the constant current power supply. An electrolyte solution containing metal salts, ammonium chloride, boric acid, sodium citrate and sodium chloride is added to the electrolytic cell. The metal salts include one or more of nickel source, cobalt source, iron source, manganese source, copper source, molybdenum source and chromium source, with a concentration range of 0.05M to 1.5M. Ammonium chloride provides an acidic environment and adjusts the pore size, with a concentration of 0.5M to 3M. Boric acid is used as a buffer with a concentration of 0.1M to 1M. Sodium citrate is used as a complexing agent with a concentration of 0.1M to 2M. Sodium chloride is used as a conductive agent with a concentration of 0.05M to 0.5M. Nickel sources can be selected from nickel chloride, nickel sulfate, nickel acetate, etc. Iron sources include ferric chloride, ferrous chloride, ferrous sulfate, ferrous sulfate, ferrous nitrate or ferrous nitrate, etc. Cobalt sources include cobalt chloride, cobalt sulfate, cobalt acetate, cobalt nitrate, etc. Manganese sources include manganese chloride, manganese sulfate, manganese acetate, manganese nitrate, etc. Copper sources include copper chloride, copper sulfate, copper acetate, copper nitrate, etc. Molybdenum sources include sodium molybdate and ammonium molybdate, etc. Chromium sources include chromium chloride, chromium sulfate, chromium acetate and or chromium nitrate, etc. The present invention can adjust the morphology of the catalyst by adjusting the type and concentration of the above-mentioned metal salts to form a rougher and more open structure, thereby optimizing the catalytic performance, and the use of non-precious metal salts can reduce the cost of the catalyst. Unlike traditional electrodeposition methods, in the present invention, when a large current is applied to the cathode and the anode, the hydrogen evolution reaction and the metal salt reduction reaction are carried out simultaneously. Due to the generation of hydrogen bubbles, these bubbles will adhere to the surface of the electrode and form gaps. In the areas where the bubbles exist, due to the barrier effect of the bubbles, the sediment cannot cover these areas, so these areas will form gaps and form a porous structure. During the electrodeposition process, the shedding of bubbles and the deposition of metals are carried out alternately, so that the final deposit has a three-dimensional structure and contains a large number of pores, which can provide a large specific surface area, thereby improving the efficiency of the catalytic reaction. By depositing multiple metal ions in the electrolyte at the same time, a multi-element alloy catalyst can be formed.
[0049] During the electrodeposition process, a constant current of 0.5 A / cm was applied. 2 ~3A / cm 2 , the deposition time is 15s~1200s.
[0050] The time and current density of electrodeposition have a significant impact on the structure and performance of the catalyst. If the electrodeposition time is short, the amount of catalyst deposited is insufficient and it is difficult to form a rich structure; while too long an electrodeposition time leads to an overly thick coating, which in turn causes the loss of part of the pore structure, thereby reducing the specific surface area. A lower electrodeposition current density results in less hydrogen evolution, and it is difficult for the catalyst to form a porous structure; while a higher current density may cause the catalyst to fall off the surface of the substrate. Therefore, optimizing the electrodeposition time and current density is the key to achieving high performance of the catalyst.
[0051] By adjusting the type and concentration of metal salts, the morphology of the catalyst is further optimized to form a three-dimensional porous multi-element alloy catalyst with an open structure. Finally, the three-dimensional void structure of the matrix, the catalyst is not only deposited on the outer surface of the matrix, but also enters the pores of the matrix. The deposition of the catalyst occurs on the surface and pore wall of the nickel foam. The electrode is removed from the electrolytic cell, repeatedly rinsed with deionized water, and naturally dried to obtain a three-dimensional porous multi-element alloy catalyst.
[0052] Reaction that occurs: Hydrogen evolution reaction: 2H++2e - →H2
[0053] Electrodeposition reaction (reduction reaction)
[0054] The electrodeposition process is to deposit metal ions or other materials onto the electrode surface through an electrochemical reduction reaction. Taking NiCo alloy as an example, the general reaction of its electrodeposition process is as follows: Electrodeposition reaction of metal nickel and cobalt:
[0055] Ni 2+ +2e - →Ni
[0056] Co 2+ +2e - →Co
[0057] x 2+ +yCo 2+ +2e - → NixCoy
[0058] Hydrogen bubbles are generated on the surface of the substrate. These bubbles are attached to the electrode surface and form voids. In the areas where bubbles exist, the deposits cannot cover these areas due to the barrier effect of the bubbles, so these areas will form voids and form porous nanostructures. The distribution of bubbles on the electrode surface and their aggregation state play a decisive role in the formation of the final porous structure. By adjusting the current density, time, bubble introduction method and electrolyte composition of the electrodeposition, the porosity and pore size distribution of the deposit can be precisely controlled. By depositing multiple metal ions in the electrolyte at the same time, a multi-element alloy catalyst can be formed. During the electrodeposition process, the detachment of bubbles and the deposition of metals are carried out alternately, so that the final deposit has a three-dimensional structure and contains a large number of pores, which can provide a large specific surface area, thereby improving the efficiency of the catalytic reaction.
[0059] The present invention adopts a dynamic bubble template electrodeposition method to synthesize a three-dimensional porous non-precious metal multi-element alloy nanostructure catalyst in one step quickly and efficiently. The non-precious metal is a metal salt added to the electrolyte, nickel, cobalt, iron, copper, manganese, chromium, and molybdenum, which has a significant price advantage over precious metal catalysts, and the raw materials are widely available; the preparation process is simple, fast, and efficient, and does not involve complex process flows such as hydrothermal or solvent thermal and high-temperature heating, which simplifies the catalyst preparation process and can prepare catalysts on a large scale for industrial production. By adjusting the composition of the electrolyte to optimize the microscopic morphology of the catalyst, the prepared three-dimensional porous catalyst has a high specific surface area nanostructure, which can expose more active sites, optimize the contact with the electrolyte, and promote the release of gas. The prepared three-dimensional porous multi-element alloy catalyst does not need to use a binder, enhances the interfacial charge transfer performance, and effectively accelerates the reaction kinetics. In addition, the synergistic effect of the metal elements in the multi-element alloy adjusts the electronic structure and improves the conductivity. The three-dimensional porous non-precious metal multi-element alloy catalyst prepared by the present invention exhibits excellent electrochemical catalytic activity and stability in the process of hydrogen production by electrolysis of water at high current density, and can be used for large-scale industrial application of hydrogen production by alkaline electrolysis of water at high current density.
[0060] As an embodiment disclosed in the present invention, the present invention also provides a three-dimensional porous multi-element alloy catalyst, which is obtained by the described method. The pore size range of the catalyst is 5 to 50 μm, and it presents nanostructures such as "cauliflower", "nanoflower" and "nanosheet".
[0061] The method of the present invention will be described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments.
[0062] Unless otherwise specified, the reagents, methods, instruments and equipment used in the present invention are conventional reagents, methods, instruments and equipment in the art. Unless otherwise specified, the reagents and materials used in the following examples are commercially available and of analytical grade.
[0063] Example 1
[0064] A method for preparing a three-dimensional porous NiCo alloy bifunctional catalyst for water electrolysis comprises the following steps:
[0065] (1) The nickel mesh was first ultrasonically treated in acetone for 20 min to remove surface oil, and then rinsed three times with deionized water. Then, it was ultrasonically cleaned in 3M HCl for 20 min to remove surface oxides, and then rinsed repeatedly with deionized water until the pH was neutral. Finally, it was ultrasonically treated in anhydrous ethanol for 20 min and dried naturally for use.
[0066] (2) Figure 1The flow chart of the preparation method of three-dimensional porous bifunctional catalyst electrode. Taking the preparation of NiCo catalyst as an example, a two-electrode system is adopted. The pretreated nickel mesh is used as the working electrode, which is connected to the negative electrode of the constant current power supply, and the platinum sheet is used as the counter electrode, which is connected to the positive electrode of the constant current power supply. The electrolyte solution includes 0.5M nickel chloride, 0.5M cobalt chloride, 1.5M ammonium chloride, 0.2M boric acid, 0.2M sodium citrate and 0.05M sodium chloride. The current density is 2A / cm 2 , the deposition time is 90s. During the catalyst preparation process, the metal ion Ni 2+ 、Co 2+ Deposition and hydrogen evolution occur simultaneously. The porous nanostructure of the catalyst is gradually formed under the conditions of strong hydrogen evolution on nickel foam. After the prepared catalyst is taken out of the electrolyzer, it is repeatedly rinsed with deionized water for several times and then dried naturally to obtain a three-dimensional porous NiCo / NM alloy bifunctional catalyst.
[0067] (3) Taking the NiCo / NM water splitting catalyst obtained in this example as an example, SEM analysis was performed. Figure 2 As shown in Figure 1, it presents a three-dimensional porous interconnected structure with a pore size range of 10 to 50 μm. Further observation shows that the NiCo alloy catalyst presents a unique dendrite nanosheet structure, with dendritic deposits growing in all directions and interlocking to form a structure with excellent mechanical properties. Further observation using a transmission electron microscope, such as Figure 3 As shown, it also presents a dendritic nanosheet structure. This high surface area can enhance the exposure of active sites. The electrochemical test was carried out using a Gamry Reference 600+ electrochemical workstation in a standard three-electrode system with 1MKOH as the electrolyte. A high-purity graphite rod was used as the counter electrode, the Hg / HgO electrode was used as the reference electrode, and the prepared NiCo / NM catalyst was used as the working electrode. The catalytic activity of NiCo / NM in hydrogen evolution reaction and oxygen evolution reaction was determined by linear sweep voltammetry (LSV) at a scan rate of 2 mV / s. All LSVs were corrected with 95% iR. The HER and OER current-voltage scanning curves of the NiCo / NM catalyst are shown in Figure 2. Figure 4 As shown, at a current density of 100 mA / cm 2 and 500mA / cm 2 At a current density of 100 mA / cm, the HER overpotentials are 236.3 mV and 306.2 mV respectively. 2 and 500mA / cm 2At a current density of 1.34 W / m, the OER overpotentials are 373.0 mV and 446.8 mV, respectively. It can be seen that the three-dimensional porous NiCo / NM alloy catalyst electrode prepared by the present invention still maintains a low overpotential at a high current density, showing excellent catalytic performance. In order to prove that NiCo / NM has the ability to act as a bifunctional catalyst, the prepared samples were directly used as anodes and cathodes to make a two-electrode system electrolyzer. The current-voltage scanning curve and the 2 The long-term electrolysis curve at a current density of Figure 5 As shown in Figure 2, the NiCo / NM||NiCo / NM electrolyzer requires voltages as low as 1.77 V and 2.03 V to drive 100 mA / cm 2 and 500mA / cm 2 The current density of 100 mA / cm 2 The performance was maintained at a current density of 1.34 W for 100 h without obvious degradation, which indicates that the bifunctional catalyst has excellent stability.
[0068] Example 2
[0069] A method for preparing a three-dimensional porous CoFe binary alloy bifunctional catalyst for water electrolysis comprises the following steps:
[0070] (1) The nickel foam was first ultrasonically treated in acetone for 20 min to remove surface oil, and then rinsed three times with deionized water. Then, it was ultrasonically cleaned in 3M HCl for 20 min to remove surface oxides, and then rinsed repeatedly with deionized water until the pH was neutral. Finally, it was ultrasonically treated in anhydrous ethanol for 20 min and dried naturally for use.
[0071] (2) A two-electrode system was used, with the pretreated nickel foam as the working electrode, connected to the negative electrode of the constant current power supply, and the platinum sheet as the counter electrode, connected to the positive electrode of the constant current power supply. The electrolyte solution included 0.5 M cobalt chloride, 0.5 M ferrous sulfate, 2 M ammonium chloride, 0.2 M boric acid, 0.2 M sodium citrate and 0.05 M sodium chloride. The current density was 1.5 A / cm 2 , the deposition time is 300s. During the catalyst preparation process, the metal ion Fe 2+ 、Co 2+ Deposition and hydrogen evolution occur simultaneously. The porous nanostructure of the catalyst is gradually formed under the conditions of strong hydrogen evolution on nickel foam. After the prepared catalyst is taken out of the electrolytic cell, it is repeatedly rinsed with deionized water for many times and then dried naturally to obtain a three-dimensional porous CoFe binary alloy bifunctional catalyst.
[0072] (3) Taking the CoFe / NF OER catalyst obtained in this example as an example, SEM analysis was performed. Figure 6 As shown, it presents a three-dimensional porous interconnected structure with a pore size range of 5 to 15 μm. Further observation showed that the CoFe alloy catalyst exhibited a unique "nanoflower" structure, and interlocked to form a structure with excellent mechanical properties. The electrochemical test was carried out using a Corr Test CS350M electrochemical workstation in a standard three-electrode system with 1M KOH as the electrolyte. A high-purity graphite rod was used as the counter electrode, a Hg / HgO electrode was used as the reference electrode, and the prepared CoFe / NF catalyst was used as the working electrode. The catalytic activity of the oxygen evolution reaction of the sample was determined by linear sweep voltammetry (LSV) at a scan rate of 5 mV / s. All LSV curves were corrected with 95% iR. The OER current-voltage scanning curve of CoFe / NF is shown in the figure. Figure 7 As shown, it shows that at a current density of 1000mA / cm 2 and 2000mA / cm 2 At current densities of , the OER overpotentials are 332 mV and 376 mV, respectively.
[0073] Example 3
[0074] A method for preparing a three-dimensional porous NiFe binary alloy bifunctional catalyst for water electrolysis comprises the following steps:
[0075] (1) The nickel foam was first ultrasonically treated in acetone for 20 min to remove surface oil, and then rinsed three times with deionized water. Then, it was ultrasonically cleaned in 3M HCl for 20 min to remove surface oxides, and then rinsed repeatedly with deionized water until the pH was neutral. Finally, it was ultrasonically treated in anhydrous ethanol for 20 min and dried naturally for use.
[0076] (2) A two-electrode system was used, with the pretreated nickel foam as the working electrode, connected to the negative electrode of the constant current power supply, and the platinum sheet as the counter electrode, connected to the positive electrode of the constant current power supply. The electrolyte solution included 0.5 M nickel cobalt, 0.5 M ferrous sulfate, 2 M ammonium chloride, 0.2 M boric acid, 0.2 M sodium citrate and 0.05 M sodium chloride. The current density was 1.5 A / cm 2 , the deposition time is 300s. During the catalyst preparation process, the metal ion Ni 2+ , Fe 2+ Deposition and hydrogen evolution occur simultaneously. The porous nanostructure of the catalyst is gradually formed under the conditions of strong hydrogen evolution on the nickel foam. After the prepared catalyst is taken out of the electrolytic cell, it is repeatedly rinsed with deionized water for many times and then dried naturally to obtain a three-dimensional porous NiFe binary alloy bifunctional catalyst.
[0077] (3) Taking the NiFe / NF OER catalyst obtained in this example as an example, SEM analysis was performed. Figure 8As shown, it presents a three-dimensional porous interconnected structure with a pore size range of 5 to 15 μm. Further observation showed that the NiFe alloy catalyst exhibited a unique "cauliflower" structure, and interlocked to form a structure with excellent mechanical properties. The electrochemical test was carried out using a Corr Test CS350M electrochemical workstation in a standard three-electrode system with 1M KOH as the electrolyte. A high-purity graphite rod was used as the counter electrode, a Hg / HgO electrode was used as the reference electrode, and the prepared CoFe / NF catalyst was used as the working electrode. The catalytic activity of the oxygen evolution reaction of the sample was determined by linear sweep voltammetry (LSV) at a scan rate of 5 mV / s. All LSVs were corrected for 95% iR. The OER current-voltage scan curve of NiFe / NF is shown in the figure. Fig. 9 As shown, it shows that at a current density of 1000mA / cm 2 and 2000mA / cm 2 At current densities of , the OER overpotentials are 312 mV and 355 mV, respectively.
[0078] Example 4
[0079] A method for preparing a three-dimensional porous NiCoFe ternary alloy bifunctional catalyst for water electrolysis comprises the following steps:
[0080] (1) The nickel foam was first ultrasonically treated in acetone for 20 min to remove surface oil, and then rinsed three times with deionized water. Then, it was ultrasonically cleaned in 3M HCl for 20 min to remove surface oxides, and then rinsed repeatedly with deionized water until the pH was neutral. Finally, it was ultrasonically treated in anhydrous ethanol for 20 min and dried naturally for use.
[0081] (2) A two-electrode system was used, with the pretreated nickel foam as the working electrode, connected to the negative electrode of the constant current power supply, and the platinum sheet as the counter electrode, connected to the positive electrode of the constant current power supply. The electrolyte solution included 0.5M nickel chloride, 0.5M cobalt chloride, 0.5M ferrous sulfate, 2M ammonium chloride, 0.2M boric acid, 0.2M sodium citrate and 0.05M sodium chloride. The current density was 1.5A / cm 2 , the deposition time is 300s. During the catalyst preparation process, the metal ion Ni 2+ 、Co 2+ , Fe 2+ Deposition and hydrogen evolution occur simultaneously. The porous nanostructure of the catalyst is gradually formed under the conditions of strong hydrogen evolution on the nickel foam. After the prepared catalyst is taken out of the electrolyzer, it is repeatedly rinsed with deionized water for many times and then dried naturally to obtain a three-dimensional porous NiCoFe ternary alloy bifunctional catalyst electrode.
[0082] (3) Taking the NiCoFe / NF water splitting catalyst obtained in this example as an example, SEM analysis was performed. Fig.10As shown, it presents a three-dimensional porous interconnected structure with a pore size range of 5 to 15 μm. Further observation showed that the NiCoFe alloy catalyst exhibited a unique "cauliflower" structure, and interlocked to form a structure with excellent mechanical properties. The electrochemical test was carried out using a Corr Test CS350M electrochemical workstation in a standard three-electrode system with 1M KOH as the electrolyte. A high-purity graphite rod was used as the counter electrode, a Hg / HgO electrode was used as the reference electrode, and the prepared NiCoFe / NF catalyst was used as the working electrode. The catalytic activity of the hydrogen evolution reaction and oxygen evolution reaction of the sample was determined by linear sweep voltammetry (LSV) at a scan rate of 5 mV / s. All LSVs were corrected with 95% iR. The HER and OER current-voltage scanning curves of NiCoFe / NF are shown in Figure 2. Fig.11 As shown, it shows that at a current density of 1000mA / cm 2 and 2000mA / cm 2 At a current density of 1000 mA / cm, the HER overpotentials are 292 mV and 306 mV respectively. 2 and 2000mA / cm 2 At current densities of , the OER overpotentials are 293 mV and 334 mV, respectively.
[0083] The above description shows and describes several preferred embodiments of the present invention, but as mentioned above, it should be understood that the present invention is not limited to the form disclosed herein, and should not be regarded as excluding other embodiments, but can be used in various other combinations, modifications and environments, and can be modified within the scope of the application concept described herein through the above teachings or the technology or knowledge of the relevant field. The changes and modifications made by those skilled in the art shall not depart from the spirit and scope of the present invention, and shall be within the scope of protection of the claims attached to the present invention.
Claims
1. A method for preparing a three-dimensional porous multi-element alloy catalyst, characterized in that: The method comprises the following steps: S1. pretreating the substrate having a three-dimensional structure to obtain a pretreated substrate; S2. Connecting the pretreated substrate as a first electrode to the negative electrode of a constant current power supply, connecting the second electrode to the positive electrode of the constant current power supply, inserting the positive electrode and the negative electrode into an electrolytic cell loaded with an electrolyte solution, applying a constant current to the electrolyte solution by the constant current power supply, and performing electrodeposition on the electrolyte solution, wherein the electrolyte solution is a mixed solution including a metal salt, ammonium chloride, boric acid, sodium citrate and sodium chloride; S3. After a period of deposition, a three-dimensional porous catalyst having an open structure is formed on the surface of the pretreated substrate; S4. The three-dimensional porous catalyst is taken out from the electrolytic cell, rinsed and dried to obtain a three-dimensional porous multi-element alloy catalyst.
2. The method according to claim 1, characterized in that The pre-processing in step S1 includes: S11. The substrate was ultrasonically treated in acetone for 20 min to remove surface oil stains, and then rinsed three times with deionized water; S12. The substrate obtained in S11 was then ultrasonically cleaned in 3M HCl for 20 min and then repeatedly rinsed with deionized water until the pH was neutral; S13. The matrix obtained in S12 is ultrasonically treated with anhydrous ethanol for 20 minutes and then dried to obtain a pretreated matrix.
3. The method according to claim 1, characterized in that The substrate is one or more of nickel mesh, nickel-iron alloy mesh, copper mesh, titanium mesh, stainless steel mesh, foamed nickel, foamed iron and / or foamed copper.
4. The method according to claim 1, characterized in that: The second electrode is a platinum sheet, a graphite plate or a graphite rod.
5. The method according to claim 1, characterized in that The metal salt is one or more of a nickel source, a cobalt source, an iron source, a manganese source, a copper source, a molybdenum source, and a chromium source, and the concentration range is 0.05 to 1.5 mol / L.
6. The method according to claim 5, characterized in that The concentration of ammonium chloride is 0.5-3 mol / L; the concentration of boric acid is 0.1-1 mol / L; the concentration of sodium citrate is 0.1-2 mol / L; and the concentration of sodium chloride is 0.05-0.5 mol / L.
7. The method according to claim 5, characterized in that The nickel source is nickel chloride, nickel sulfate or nickel acetate; the iron source is ferric chloride, ferrous chloride, ferric sulfate, ferrous sulfate, ferric nitrate or ferrous nitrate.
8. The method according to claim 5, characterized in that The cobalt source is cobalt chloride, cobalt sulfate, cobalt acetate or cobalt nitrate; the manganese source is manganese chloride, manganese sulfate, manganese acetate or manganese nitrate.
9. The method according to claim 2, characterized in that: The constant current is 0.5A / cm 2 ~3A / cm 2 The deposition period is 15s to 1200s.
10. A three-dimensional porous multi-element alloy catalyst, characterized in that: The three-dimensional porous multi-element alloy catalyst is obtained by the method described in any one of claims 1 to 9. The pore size of the catalyst ranges from 5 to 50 μm, and presents a nanostructure of "cauliflower", "nanoflower" or "nanosheet".
Citation Information
Patent Citations
Catalytic assembly
CN106660013A
Multi-stage structure electrode for electrolyzing water, and preparation method of multi-stage structure electrode
CN112626540A
Three-dimensional porous Ni-Mo-Cu catalyst and preparation method and application thereof
CN114959776A
Preparation method capable of rapidly preparing efficient hydrogen evolution catalyst on carbon steel
CN115449816A
Molybdenum-nickel alloy electrocatalyst, preparation method thereof and application of electrocatalyst in hydrogen production through water electrolysis
CN115948764A